Portugal - Estanqueiro, Ana (2013)
During 2004, Portugal reversed the tendency of slow wind capacity growth observed in previous years. The publication of legislation and tariffs at the end of 2001 and subsequent government simplifi cation of administrative processes concerning the implementation of renewable energy projects resulted in nearly doubled capacity in Portugal during 2004. In the following sections, a summary of the events of the year is presented with a main focus on the current state of development and trends.